Red Cards: Not Such Bad News For Penalized Guest Teams - Mario Mechtel; Tobias Brändle; Agnes Stribeck; Karin Vetter (Verein für Socialpolitik, 2010)
An old soccer myth states that teams affected by a sending-off perform better than they would have without the penalty. Using economic theory, we analyze the course of a soccer match after a sending-off and test our hypotheses using data from the German Bundesliga from 1999 to 2009. The results show that sending-offs affecting home teams have a negative impact on their performance. However, for guest teams the impact of a sending-off on their performance depends on the time remaining after the sending-off. Thus, the ten do it better myth seems to hold for guest teams to a certain extent.
Keywords: L83; M12; M50; 330; soccer; team performance; red card; sending-off; Bundesliga